1996
DOI: 10.1002/(sici)1520-6300(1996)8:6<761::aid-ajhb8>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of menopause in relation to the timing of reproductive events and past menstrual experience

Abstract: The framework of the lifespan approach is used to examine the frequency of symptoms associated with menopause. Symptom frequencies are examined in relation to past menstrual symptom experience and the timing of reproductive events. Data were drawn from a cross‐sectional community survey carried out in Greene County, New York. The symptoms most often reported were hot flashes, irritability, mood changes, sweating, and headaches. Frequencies of vasomotor symptoms (hot flashes, sweating) were highly correlated. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…However, two studies found that earlier menarche was associated with decreased prevalence of hot flushes (<12 versus ≥12 years) or reduced odds of hot flushes (<13 versus ≥13 years), 8,9 and other studies reported no association. [10][11][12][13][14] To date, only ALSWH has examined the association with night sweats, in which 'sometimes' and 'often' categories were combined, but did not find any association. 10 There are a number of possible reasons why the results have been inconsistent, including that study participants had different racial, cultural and socio-economic backgrounds and that the measure of VMS varied from a single question to a more detailed history.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two studies found that earlier menarche was associated with decreased prevalence of hot flushes (<12 versus ≥12 years) or reduced odds of hot flushes (<13 versus ≥13 years), 8,9 and other studies reported no association. [10][11][12][13][14] To date, only ALSWH has examined the association with night sweats, in which 'sometimes' and 'often' categories were combined, but did not find any association. 10 There are a number of possible reasons why the results have been inconsistent, including that study participants had different racial, cultural and socio-economic backgrounds and that the measure of VMS varied from a single question to a more detailed history.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 A few studies have reported no associations. [10][11][12][13][14] Early menarche [15][16][17] and VMS [18][19][20] have been associated with an increased risk of cardiovascular diseases, type 2 diabetes and breast cancer in later life. Adult obesity may be part of the mechanism linking early menarche with these disease risks.…”
Section: Introductionmentioning
confidence: 99%
“…Data were drawn from a study of variation in age at menopause carried out in Greene County, New York (1989, primarily among European-American women. The study sample is an opportunity sample in that participants were recruited from community organizations, school districts, health care institutions, or county offices (Leidy, 1991(Leidy, , 1996. The sample includes 376 women, 85 of whom underwent a hysterectomy.…”
Section: Sample and Methodsmentioning
confidence: 99%
“…Similarly, the correlates of menopausal symptoms are variable. Symptoms of menopause have been associated with smoking habits (Dennerstein et al, 1993), socioeconomic status (Wilbur et al, 1998), education level (Avis et al, 1997), parity (Beyene, 1989), prolonged lactation (Lancaster and King, 1992), history of premenstrual symptoms (Leidy, 1996;Skarsgard et al, 1996), phytoestrogens in the diet (Aldercreutz et al, 1992;Knight et al, 1996), the medicalization of menopause (Obermeyer, 2000), stressful life events (Hunter, 1993), and attitudes toward menstruation, menopause, and aging (Avis and McKinlay, 1991;Lock, 1993). Such variability may argue against the use of the symptoms of menopause as a measure of population health, particularly for comparisons of health across populations, but also indicates the need for comprehensive, biocultural approaches to the study of menopause.…”
Section: Symptom Experience At Menopausementioning
confidence: 99%